(untitled) (CIPEEX, 2024)
THE AIM OF THIS STUDY WAS TO PROMOTE A LITERATURE REVIEW ON TOXOPLASMOSIS AND ITSCONSEQUENCES IN PRIME INFECTION DURING PREGNANCY. A BIBLIOGRAPHIC REVIEW OF THE NARRATIVETYPE WAS PROMOTED WITH RESEARCH OF SCIENTIFIC ARTICLES IN THE DATABASES SCIELO, PUBMED ANDGOOGLE SCHOLAR, USING THE KEYWORDS: TOXOPLASMOSIS, TOXOPLASMA GONDII, CONGENITALTOXOPLASMOSIS AND PREGNANCY. PUBLICATIONS IN ENGLISH WERE INCLUDED IN THE STUDY ANDPORTUGUESE MADE AVAILABLE IN FULL WITHIN FIVE YEARS. FROM THIS LITERATURE REVIEW IT WAS VERIFIEDTHAT TOXOPLASMOSIS IS A PROTOZOOSIS CAUSED BY THE PARASITE TOXOPLASMA GONDII. ITSTRANSMISSION OCCURS AFTER THE INGESTION OF SPORULATED OOCYSTS OF T. GONDII, WHICH ARE RELEASEDINTO THE ENVIRONMENT AFTER PERFORMING SEXUAL CYCLE IN FELINES, BEING ELIMINATED IN THE FECES OFCONTAMINATED CATS. THUS, THEY MAY BE PRESENT IN CONTAMINATED WATER DUE TO LACK OF BASICSANITATION, CONSUMPTION OF RAW OR UNDERCOOKED MEAT AND CONTACT WITH INFECTED SAND, AMONGOTHERS. VERTICAL TRANSMISSION OCCURS BY TRANSPLACENTAL ROUTE AND IS CALLED CONGENITALTOXOPLASMOSIS. EACH REGION HAS A DEMOGRAPHIC CHARACTERISTIC THAT CAN INFLUENCE THE INCREASEIN INFECTION. PREGNANT WOMEN WITH TOXOPLASMOSIS IN THE ACUTE PHASE MAY PRESENT WITHSYMPTOMS SUGGESTIVE OF PRIMARY INFECTION, ESPECIALLY FEVER, HEADACHE, LYMPH NODEENLARGEMENT, ASTHENIA, MYALGIA, AND SORE THROAT. CONGENITAL TOXOPLASMOSIS CAN CAUSE A FEWCONSEQUENCES FOR THE FETUS, SUCH AS PREMATURE BIRTH, INTELLECTUAL DISABILITY, SEVEREDEVELOPMENTAL DELAYS, INTRAUTERINE GROWTH RESTRICTION, JAUNDICE, HEPATOSPLENOMEGALY,INTRACRANIAL CALCIFICATIONS, HYDROCEPHALUS OR RETINOCHOROIDITIS. BECAUSE IT HAS A MAJOR IMPACTON HUMAN HEALTH, TOXOPLASMOSIS REQUIRES PROPER SCREENING, DIAGNOSIS, AND TREATMENT TOPREVENT OR MINIMIZE ITS POTENTIAL DAMAGE. STUDIES HAVE REPORTED ON THE PREVALENCE OFCONGENITAL INFECTION BY T. GONDII TO BE BETWEEN 0.6-1.3/1000 LIVE BIRTHS IN BRAZIL. IT WASSUGGESTED THAT THE CHANCE OF TRANSPLACENTAL TRANSMISSION, THAT IS, FROM MOTHER TO FETUS ISVARIABLE BETWEEN 18.5 AND 23%. THE RISK OF FETAL INFECTION IN THE FIRST TRIMESTER IS LESS THAN15%, BUT IN GENERAL, THE DISEASE IS SEVERE IN THE NEWBORN. THE RISK OF INFECTION INCREASESBETWEEN 20 AND 50% IN THE SECOND TRIMESTER AND BETWEEN 55 AND 80% IN THE THIRD TRIMESTEROF PREGNANCY, BUT THE NEWBORN IS ASYMPTOMATIC OR HAS LESS SEVERE DISEASE. PRIMARY HEALTHCARE (PHC) IS CONSIDERED THE GATEWAY TO HEALTH SERVICES AND HAS GREAT RELEVANCE IN THEINFORMATION TRANSMITTED FOR THE MONITORING OF CASES IN MULTIDISCIPLINARY TEAMS, BEING DETERMINANT FOR THE CHANGE OF BEHAVIORS AND FOR THE ADOPTION OF HEALTHY LIFESTYLE HABITS. IT WAS CONCLUDED THAT TOXOPLASMOSIS IS AN IMPORTANT PUBLIC HEALTH PROBLEM, ESPECIALLY WHEN IT CAUSES HARM TO THE FETUS THROUGH VERTICAL TRANSMISSION; SHOULD BE STUDIED AND ORIENTED TO THEPOPULATION AND ESPECIALLY PREGNANT WOMEN, BECAUSE IT IS A COMMON DISEASE AND PREVENTIONAND SYMPTOMS OFTEN UNKNOWN.